Fabrication and in vitro characterization of polycaprolactone/graphene oxide/collagen nanofibers for myocardial repair - ULAĞ, SONGÜL; ŞAHİN, ALİ; DUMLUDAĞ, FATİH; GÜNDÜZ, OĞUZHAN (My University, 2023)
This study is focused on fabricating tissue-engineered electrospun nanofibers that contain polycaprolactone (PCL), graphene oxide (GO), and collagen (COL) to get an alternative treatment for cardiac injuries. GO (1.5 wt%) is used to support the contraction-elongation of cardiomyocytes by improving electrical stimulation. The COL (1, 3, and 5 wt%) is the main component of the myocardial extracellular matrix have led to their frequent use in cardiac tissue engineering (CTE). The scanning electron microscope (SEM) images show the homogeneous and bead-free morphologies of the nanofibers. Adding a high amount (3% and 5%) of COL decreases the tensile strength value of 17% PCL/1.5% GO nanofiber. 3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide (MTT) assay demonstrates that the COL addition increases cell viability compared to that in 17% PCL/1.5% GO nanofibers on the third day. The response of the nanofibers to alternating current (AC) signal is studied between the frequencies 40 and 105 Hz. The direct current (DC) conductivity values of the films are determined to be between 1.10−10 and 6.10−10 S m−1 at 25 °C. The AC conductivity values show frequency-dependent behavior. Among the PCL/GO-based electrospun nanofibers, 17% PCL/1.5% GO/5% COL nanofiber shows greater DC and AC conductivity than 17% PCL/1.5% GO nanofiber.
Keywords: Kimya Mühendisliği ve Teknolojisi; Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Malzeme Bilimi; MÜHENDİSLİK, KİMYASAL; POLİMER BİLİMİ; KİMYA, ORGANİK; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; MATERIALS SCIENCE; CHEMISTRY; ENGINEERING, CHEMICAL; POLYMER SCIENCE; CHEMISTRY, ORGANIC; MATERIALS SCIENCE, MULTIDISCIPLINARY; Genel Kimya Mühendisliği; Fizik Bilimleri; Polimerler ve Plastikler; Organik Kimya; Malzeme Kimyası; General Chemical Engineering; Physical Sciences; Polymers and Plastics; Organic Chemistry; Materials Chemistry; collagen; conductivity; electrospinning; graphene oxide; myocardial tissue; nanofiber; polycaprolactone